KONDISI FISIK TANAH HUTAN MANGROVE DI DESA DOLAGO KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Azis, Ramli; Korja, I Nengah; Toknok, Bau (Jurnal Warta Rimba, 2017)
The objective of the research was to find out soil physical condition of Mangrove Forest in Â Dolago village South Parigi Subdistrict Parigi Moutong District. The research was conducted on January to March 2016 that located in Dolago village, South Parigi Subdistrict, Parigi Moutong District. The method of taking sample was purposive sampling, soil sample taken from each mangrove stand, the dominant ones were Sonneratia alba, Rhizophora sp and shifting between Sonneratia alba, and Rhizophora sp . The soil sample was analyzed in Agronomy Laboratory of Forestry Faculty of Tadulako University, and the measurement of mud depth was done in the location directly. The result of soil sample analysis from laboratory showed that soil pH on Sonneratia alba stand was 6,20, Rhizophora sp was 6,03 and shifting was 6, 10, The soil color on Sonneratia alba stand was dark grey, Rhizophora sp was dark grey and shifting between Sonneratia alba, and Rhizophora sp was very dark grey, the soil texture of the three samples under taken stands was dominated by clay sand, water salinity on Sonneratia alba stand was 2,9 ppt, Rhizophora sp 3,0 ppt, and shiftingÂ  between Sonneratia alba, and Rhizophora sp was 2,8 ppt, and mud depth that directly measured on location showed that from the tree stands reached 78 cm height.Keywords: Physical condition, Soil, and Magrove Forest.